2023
DOI: 10.1001/jamanetworkopen.2023.7004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Chuan on Cognitive Function in Adults 60 Years or Older With Type 2 Diabetes and Mild Cognitive Impairment in China

Abstract: ImportanceType 2 diabetes (T2D) is associated with the progression of cognitive dysfunction. Physical activity benefits cognition, but no evidence from randomized clinical trials has shown whether tai chi chuan has better long-term benefits than fitness walking in cognitive function for patients with T2D and mild cognitive impairment (MCI).ObjectiveTo compare the effectiveness of tai chi chuan, a mind-body exercise, for improving cognitive function in older adults with T2D and MCI, with fitness walking.Design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…While Tai Chi may not exhibit unparalleled performance compared to other forms of exercise, it presents distinct advantages in certain aspects. Recent research underscores Tai Chi’s potential as a viable cognitive treatment for older adults grappling with T2DM and mild cognitive impairment ( 4 ). Despite sharing aerobic traits with other exercises, Tai Chi’s efficacy cannot be solely attributed to its moderate intensity and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Tai Chi may not exhibit unparalleled performance compared to other forms of exercise, it presents distinct advantages in certain aspects. Recent research underscores Tai Chi’s potential as a viable cognitive treatment for older adults grappling with T2DM and mild cognitive impairment ( 4 ). Despite sharing aerobic traits with other exercises, Tai Chi’s efficacy cannot be solely attributed to its moderate intensity and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…( 4 ) Outcome measures (O) : Primary outcomes were HbA1c and FBG. Secondary outcomes included postprandial blood glucose (PBG), fasting serum insulin (FINS), index of homeostasis model assessment of insulin resistance (HOMA-IR), body mass index (BMI), the Short-Form Health Survey (SF-36), BMI, lipids-related indices (total cholesterol (TCh), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL)), cognition, balance, and emotion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 266 Exercise also helps to improve cognitive function, and a randomized clinical trial found that tai chi was more effective than fitness walking in improving cognitive function in Chinese older patients with T2DM. 267 …”
Section: Chapter 12: Comorbidities Of Diabetes In the Elderlymentioning
confidence: 99%
“…Besides, Yijinjing combined with elastic band exercise, reducing the body weight, body mass index and fat content and improving muscle function and growth hormone secretion in patients with prediabetes, can delay muscle mass loss and diabetes development [80]. Furthermore, in a randomized clinical trial including 328 patients aged 60 and above with type 2 diabetes and mild cognitive impairment, the Tai Chi Chuan group had higher Montreal cognitive assessment scores compared with the control group and the fitness walking group at 36 weeks, suggesting its potential to prevent cognitive impairment and exacerbation in senile patients with type 2 diabetes [81]. These three recent clinical trials all manifested that adverse events unrelated to the studies did not have statistically significant differences between the TCM exercises group and the other group [79][80][81].…”
Section: Physical Activitymentioning
confidence: 99%